A pedagogia das competências: estudo de caso em um curso de tecnologia da UTFPR - Boschetti, Luís Paulo Zanolla [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Comprising two chapters, this dissertation discusses, in its first chapter, on the pedagogy of competences, exposing opinions of its intellectual mentor, Philippe Perrenoud, and five Brazilian authors with opposing views, among which Acacia Zeneida Kuenzer and Marise Nogueira Ramos. The second chapter is devoted to a brief historical account of the Federal Technological University of Paraná (UTFPR), it is followed by a clearance (under the point of view of the pedagogy of competences) of the undergraduate course of Technology in Industrial Maintenance, offered on the campus Medianeira (PR). The profile of teachers, students and graduated, the legislation relating thereto and the regional labor market were also analyzed. It was concluded that, despite the clear institutional ideological orientation in favor of the pedagogy of competences (evidenced by internal regulations), the profiles of the student and graduate follow much more the fordist/taylorist paradigm than the toyotism, for the reasons listed in throughout the text.

Composta por dois capítulos, esta dissertação discorre, em seu primeiro capítulo, sobre a pedagogia das competências, expondo opiniões de seu mentor intelectual, Philippe Perrenoud, e de cinco autores brasileiros com opiniões contrárias, dentre os quais Acácia Zeneida Kuenzer e Marise Nogueira Ramos. O segundo capítulo é dedicado a um breve relato histórico da Universidade Tecnológica Federal do Paraná (UTFPR), ao que se segue uma depuração (sob o ponto de vista da pedagogia das competências) do Curso Superior de Tecnologia em Manutenção Industrial, ofertado em seu Câmpus Medianeira (PR). Foram estudados o perfil dos professores, dos alunos, dos egressos e da legislação que a eles se refere e do mercado de trabalho regional. Concluiu-se que, apesar da nítida orientação ideológica institucional a favor da pedagogia das competências (evidenciada por meio de normativas internas), os perfis do graduando e do egresso seguem muito mais o paradigma fordista/taylorista que o modelo toyotista, pelas razões elencadas ao longo do texto.
Keywords: Perrenoud, Philippe 1944; Kuenzer, Acacia Zeneida; Ramos, Marise Nogueira; Ensino profissional; Ensino tecnico - Paraná; Educação baseada na competência